RESTRUKTURISASI KURIKULUM S-1 PJKR FIK UNY BERDASARKAN RELEVANSINYA DENGANKOMPETENSI LULUSAN DAN MASUKANMASYARAKAT - Soni Nopembri, Erwin Setyo K, Herka Maya jatmika,Tri Ani Hastuti (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2006)
Abstract: The structure of S-1 PJKR programme study curriculum in 2002 FIK curriculumshows that it doesn’t reflect the importance of physical education teacher’s competence andit has not been facilitate society need (stakeholders). The existance of several law tools andbasic reference in formulating LPTK curriculum shows that there is need to form a curriculumbased on the competence and society need. Establishment of teacher and lecture law (UUGuru dan Dosen) has given significant meaning of competence and society need in theprocess of creating a curriculum for future teachers. Therefore, there is a concern to restructurethe S-1 PJKR programme study curriculum to contextualize with competence and societyneed. It can start with changing the name of the programme study into S-1 physical educationprogramme study. In afterwards the process of programme study has to be contextualizingwith the education degree (elementary, middle, etc). Vision, mission and goals of eachprogramme still need to be reviewed. The last thing is changing the subject matter groupingbased on the basic competence and society need.Keywords: curriculum, structure, relevance, competence, society need.